Edukasi dan Pendampingan Pengelolaan Sampah Anorganik Berprinsip Zero Waste System di Desa Bagik Payung Selatan Kecamatan Suralaga - Febriani, Yuyun; Azim, Muhlisun; Rafsanjani, Arief; Ramadhan, Leny; Risma Fatmayanti, Baiq (Universitas Hamzanwadi, 2024)
Bagik Payung Selatan Village is one of the villages in Suralaga District, East Lombok Regency with a dense population of over 1.2 million people spread across 10 hamlets. The high population in Bagik Payung Selatan Village causes quite high amounts of waste production which can be seen from the large amount of rubbish piled up on the side of the road and environmental cleanliness still neglected. The community in Bagik Payung Selatan Village has a low level of awareness and knowledge regarding inorganic waste management. Most of the inorganic waste is plastic waste produced daily from household waste. This community service activity aims to provide education on inorganic waste management using ecobrick techniques with zero waste system principles in Bagik Payung Selatan Village so that the local community can manage inorganic waste well. The method of educating the community is carried out by providing outreach and training in skills to make handicraft products from inorganic waste which has previously been prepared using the ecobrick technique. The results of this community service activity include public knowledge and awareness regarding ecobrick techniques, the zero waste system principles, and community creativity in managing inorganic waste increased. The community is very enthusiastic about turning household waste into multiple useful handcraft products that can be reused and sold since they have high economic value to help the local community's economy.